Analysis on Chemical Components of Woods to Predict Ethanol Production Values - Wahyu Dwianto; Fitria Fitria; Danang Sudarwoko Adi; Rumi Kaida; Takahisa Hayashi (Masyarakat Peneliti Kayu Indonesia, 2016)
This paper deals with analysis on chemical components of woods to predict ethanol production values. The aim is expected to give a reliable value of ethanol production, eliminating the effort needed to directly measure this ethanol production from each wood species. Since the data of wood chemical components is widely available, this result will be valuable in determining a potential use of a wood species as bio-ethanol feedstock. Saccharification and fermentation processes by enzymatic hydrolysis were applied for xylems derived from49 branch trees of Cibodas, 32 branch trees of Purwodadi, and 19 branch trees of Bali Botanical Gardens in Indonesia. Three major wood components were analysed, i.e. cellulose, hemicellulose, and lignin. The results show varied relationships between ethanol production and chemical components of wood. The content of cellulose in wood was not exactly related to its ethanol production. This trend was also occurred for the relationship between hemicellulose and ethanol production. However, lignin content in woods gave an expected trend where the less lignin content, the higher the ethanol production.Furthermore, the ratios of cellulose-hemicelluloses and cellulose-lignin have been quantified. The result showed that the celullose-lignin ratio can potentially be used to predict the value of ethanol production which is expressed by linear regression y = 0.0616x + 0.8341; where R² = 0.4127, x = ethanol production and y = cellulose-lignin ratio. Gymnostoma sumatranum with cellulose content of 43.8% and lignin content of 24.1% (celullose-lignin ratio of 1.8) has actual ethanol production of 12.1 mg/100mg wood meal, compared to 15.7 mg/100mg wood meal resulted from above equation. Therefore, by using its cellulose-lignin ratio, the woods having high ethanol production can be screened from literatures.